The Wire Rendezvous and Chasing Wire Technique in the Bidirectional Approach for the Percutaneous Coronary Intervention for Chronic Total Occlusion with a Single Guiding Catheter - Keisuke Nakabayashi; Daisuke Sunaga; Nobuhito Kaneko; Akihiro Matsui; Kazuhiko Tanaka; Hiroshi Ando; Minoru Shimizu (Case Reports in Cardiology)
A bidirectional approach for percutaneous coronary intervention for chronic total occlusion (CTO-PCI) using ipsilateral collaterals with a single guiding catheter limits procedural choices. The CTO of the left circumflex artery with ipsilateral collateral artery was treated by the bidirectional approach using a single guiding catheter. While the retrograde wire directly crossed the CTO lesion, the microcatheter could not pass the CTO lesion despite the conventional strategies. Therefore, we performed the wire rendezvous and chasing wire techniques. The wire rendezvous technique enables deeper retrograde guidewire progression, and the antegrade microcatheter can reach the CTO entry. The chasing wire technique enables the antegrade guidewire to pass the route made by the retrograde guidewire. These techniques might offer a possible solution for bidirectional CTO-PCI using a single guiding catheter. However, this technique should be considered as a last resort because of the risk of rapid reocclusion.